Hak Kreditur Terhadap Perubahan Kedudukan Objek Hak Tanggungan Berdasarkan Putusan Pengadilan - Iza, Amira Izatul; Hendra, Rahmad; Dasrol, Dasrol (Jurnal Ilmiah Wahana Pendidikan, 2024)
Right of Liability is a security right imposed on the right to land as referred to in Law Number 5 of 1960 concerning Basic Regulations of Agrarian Principles, along with or not along with other objects that are an integral part of the land, which gives priority to certain creditors, over other creditors. In lawsuits involving dependent rights, the Judge often decides to cancel the encumbrance of the dependent rights that are being held by creditors. This results in legal certainty and protection for the parties in the guarantee of dependent rights which in the study are creditors of the holders of dependent rights is not achieved. The purpose of this study is First, knowing the creditor's right to change the position of the object of liability based on a court decision, Second knowing the legal protection for creditors against changes in the position of the object of liability based on a court decision. The type of research used is normative legal research using library materials as data and reference sources. This research requires secondary data consisting of primary, secondary, and tertiary legal materials. The data collection technique used in this normative legal research is library research or document study. The results of this data analysis will be concluded using deductive methods. From the results of discussion and research, there is a need for legal protection both preventively and repressively to creditors if the land rights that are the object of the dependent rights are removed which results in the position of the object of the dependent rights changing and the position of precedence (droit de preference) for holders of dependent rights who have special guarantees changes to general debt guarantees (Article 1131 of the Civil Code) so that the creditors related Does not have strong security rights and legal certainty related to the condition that debts will be repaid.